Interdepartmental Interaction for the Recovery of Claims in the Common Transit Procedure - Kapitanets, Svitlana Volodymyrivna; Kurylov, Viktor Anatoliiovych (Університет митної справи та фінансів, 2023)
The purpose of the article is to study the peculiarities of interagency cooperation in the feld of claims (debt) collection in the course of the joint transit procedure. The study was carried out using the methods of synthesis and analysis, deduction and induction, comparison (to review the existing conceptual framework, to establish the prerequisites and approaches to debt collection in the context of the common transit procedure), comparative analysis (to identify problematic aspects of implementation of certain provisions of customs and tax legislation), and generalization (to formulate the conclusions of the study). The following results were obtained in the course of the study. There were identifed the main aspects of the formation of a debt collection mechanism in the joint transit procedure in accordance with international standards. The author notes that it is advisable to consider a model of the debt collection mechanism under Annex IV of the Convention, which will be based on the interaction of customs and tax authorities. In this regard, it seems appropriate to approve the provision on the interaction of these authorities during the debt collection procedure in accordance with international standards. The author also considers the need to adopt a regulatory act approving the said regulation, to decide on the structural units of the customs and tax authorities that will be responsible for contacts with other Member States in relation to mutual assistance for other categories of taxes and duties, as well as to determine the central executive authority to which the main responsibility for contacts with other Member States in the feld of mutual assistance regulated by Directive 2010/24/EU will be delegated.

У статті розглянуто особливості здійснення міжвідомчої взаємодії щодо стягнення за вимогами (боргу) при процедурі спільного транзиту. Дослідження проведене із застосуванням методів синтезу та аналізу, дедукції та індукції, порівняння (для перегляду існуючого  понятійного апарату, встановлення передумов та підходів щодо стягнення за вимогами у контексті процедури спільного транзиту), компаративний аналізу (для виявлення проблемних аспектів реалізації окремих положень митного та податкового законодавства), узагальнення (для формування висновків дослідження). Під час дослідження отримано наступні результати. Виокремлено основні аспекти формування механізму стягнення боргу при процедурі спільного транзиту відповідно до міжнародних норм. Зауважено на доцільності розгляду моделі механізму стягнення за вимогами у рамках доповнення IV Конвенції, яка базуватиметься на взаємодії митних та податкових органів У зв’язку з цим, вбачається доречним затвердження положення про взаємодію цих органів під час процедури стягнення боргу відповідно до міжнародних норм. Також розглянуто необхідність ухвалення нормативно-правовим актом, який затвердить згадане положення, рішення щодо структурних підрозділів митного та податкового відомств, які будуть відповідати за контакти з іншими державами-членами стосовно взаємної допомоги для інших категорій податків і зборів, а також визначення центрального органу виконавчої влади, котрому буде делеговано основну відповідальність за контакти з іншими державами-членами у сфері взаємної допомоги, яку регулює Директива 2010/24/ЄС.
Keywords: recovery of claims, debt, joint transit procedure, interagency cooperation, administrative assistance, customs legislation, tax legislation; стягнення за вимогами, борг, процедура спільного транзиту, міжвідомча взаємодія, адміністративна допомога, митне законодавство, податкове законодавство